PENGGUNAAN MEDIA PLASTISIN SEBAGAI ALTERNATIF PENGGANTI MOLYMOD UNTUK MENINGKATKAN HASIL BELAJAR PSIKOMOTORIK SISWA PADA POKOK BAHASAN STRUKTUR SENYAWA ALKANA, ALKENA DAN ALKUNA - Indiatiningsih Indiatiningsih (Inteligensi : Jurnal Ilmu Pendidikan, 2020)
This research aims to describe the use of plasticine learning media to improve psychomotor learning outcomes of students on the subject matter of the structure of alkenes and alkunes 11th class MIPA 3 in SMAN 8. The structure of alkanes and alkunes, which is one of the abstract Chemical topis, so that this topics is not understood by many students. This requires the teacher’s creativity to be able to explain concrretely. So that the teacher must use a variety of interesting media, to solve this problem the teacher tries to teach the stucture of alkenes and alkunes using plasticine media. The use of plasticine media is expected to overcome problems in the field. This research is ClassroomAction Research. The instruments used ware observation sheets, reports on the practice of making stucture of alkanes, alkenes and alkunes. Data reduction, in general, all indicators of skills increase, especially indicators of cooperation and responsibility has increased significantly. Cycle II in this research obtain 98 for the highest score and 80 for the lowest score which is the use of plasticine in learning the structure of hydrocarbon compounds, especially alkene, is quite effective because this material is quite flexible compared to the use of molymod which is done in the first cycle which takes a long time to install, besides that plasticine is quite cheap and easy to obtain.